3D micro–meso-structured iron-based hybrid for peroxymonosulfate activation: performance, mechanism and comprehensive practical application potential evaluation. Issue 11 (8th September 2022) - Chen, Yanling; Chen, Yajie; Bai, Xue
Abstract : It is the first time to comprehensively assess the practical application potential of MIL-88A-CS beads from multiple perspectives. Abstract : Metal–organic frameworks (MOFs) have been demonstrated to be promising catalysts in advanced oxidation processes (AOPs), while the poor recyclability due to the powder form limits their practical application. Herein, MIL-88A was successfully embedded in a chitosan matrix for the first time to form 3D micro–meso-structured beads (MIL-88A-CS) by an in situ growth method and the beads were used as heterogeneous peroxymonosulfate (PMS) activators to degrade tetracycline hydrochloride (TC-HCl). 97.1% TC-HCl was removed by the MIL-88A-CS/PMS system in 60 min. The main parameters affecting the TC-HCl degradation efficiency were studied. The sulfate radical (SO4 ˙ − ) and hydroxyl radical (˙OH) played dominant roles in the TC-HCl removal. The possible TC-HCl degradation mechanism of the MIL-88A-CS/PMS system was proposed. The excellent catalytic activity of MIL-88A-CS was attributed to the abundant Fe active sites, –COOH groups, and large specific surface area, as well as microporous and mesoporous structures. Reasonable degradation pathways were analyzed by identifying TC-HCl intermediates. Significantly, it is the first time to comprehensively assess the practical application potential of the MIL-88A-CS beads from the perspectives of ecotoxicity, reusability, stability, TC-HCl removal efficiency in actual water environments, and economic applicability. This work provides a promising PMS activator for the removal of emerging contaminants and promotes the practical application of MOFs in wastewater treatment.